2011
DOI: 10.1016/j.anpedi.2011.06.004
|View full text |Cite
|
Sign up to set email alerts
|

La prueba de cribado del inventario de desarrollo de Battelle para la detección precoz de alteraciones del desarrollo en parálisis cerebral

Abstract: The deficit in development associated with cerebral palsy can be quantified at early ages through the use of a brief development scale, thus we propose that the systematic implementation of protocols with this screening tool would be helpful for treatment and early intervention. This would also help in anticipating and establishing the means for the multidisciplinary actions required, and could provide guidance to other health professionals, to provide adequate school, social, and family support,.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
8
0
7
Order By: Relevance
“…The age equivalent range and the actual age of the child allowed for the developmental quotient to be calculated for each child. Based on the results obtained in each case, children were considered to have developmental delay when the developmental quotient for the total score was less than 100 (the upper range limit of the final BDI equivalent age was considered for this calculation; Moraleda-Barreno, Romero-Lopez, & Cayetano-Menendez, 2011). To complete the analysis, a new dichotomous dependent variable was defined summarizing the result achieved in the Battelle Developmental Inventory in each case: A score less than 100 was defined as "no pass" (interpreted as presence of developmental delay), while a score higher than 100 was defined as "pass" (interpreted as absence of developmental delay).…”
Section: Instrumentsmentioning
confidence: 99%
“…The age equivalent range and the actual age of the child allowed for the developmental quotient to be calculated for each child. Based on the results obtained in each case, children were considered to have developmental delay when the developmental quotient for the total score was less than 100 (the upper range limit of the final BDI equivalent age was considered for this calculation; Moraleda-Barreno, Romero-Lopez, & Cayetano-Menendez, 2011). To complete the analysis, a new dichotomous dependent variable was defined summarizing the result achieved in the Battelle Developmental Inventory in each case: A score less than 100 was defined as "no pass" (interpreted as presence of developmental delay), while a score higher than 100 was defined as "pass" (interpreted as absence of developmental delay).…”
Section: Instrumentsmentioning
confidence: 99%
“…Studies that evaluate the development of motor skills variable in students using the Battelle Developmental Inventory (Newborg, Stock, & Wnek, 1996) as an instrument of diagnostic aid correlate that the students with development of motor skills suitable for their age present a greater cognitive development and language of the same level according to their age (Campo Ternera, 2010). However, studies that compare low development of motor skills score through the Battelle inventory of children with disabilities resulted in significantly lower values than of clinically healthy children (Moraleda-Barreno, Romero-López, & Cayetano-Menéndez, 2011;Moreno-Villagómez et al, 2014;Sanz Lopez, Guijarro Granados, & Sanchez Vazquez, 2007). When reviewing the state of the art research in people with disabilities, it has been showed that physical activity on a regular basis contributes to an improvement in coordination of motor skills (Pulzi & Rodrigues, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…No GE-II 75% apresentou MBP (≤ 1500g) e 25% BP (>1500g a ≤ 2500g). Estudos evidenciaram que crianças de MBP são mais vulneráveis a distúrbios do desenvolvimento (MAGALHAES et al, 1999;EHRENKRANZ, 2000;PETERSONS, et al, 2000;MANCINI et al, 2002;MÉIO et al, 2003;CHERMONT et al, 2005;RUGOLO, 2005;FOSTER-COHEN et al, 2007;KESSEL-FEDDEMA et al, 2007;RESIC et al, 2008;LIERDE et al, 2009;SALGE et al, 2009;LEMOS et al, 2010;BARRE et al, 2011;MORALEDA-BARRENO et al, 2011;MOORE et al, 2012;BALLOT et al, 2012).…”
Section: Discussionunclassified